2019
DOI: 10.1364/oe.27.000a81
|View full text |Cite
|
Sign up to set email alerts
|

Improved solar hydrogen production by engineered doping of InGaN/GaN axial heterojunctions

Abstract: InGaN-based nanowires (NWs) have been investigated as efficient photoelectrochemical (PEC) water splitting devices. In this work, the InGaN/GaN NWs were grown by molecular beam epitaxy (MBE) having InGaN segments on top of GaN seeds. Three axial heterojunction structures were constructed with different doping types and levels, namely n-InGaN/n-GaN NWs, undoped (u)-InGaN/p-GaN NWs, and p-InGaN/p-GaN NWs. With the carrier concentrations estimated by Mott-Schottky measurements, a PC1D simulation further confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…Afterwards, this group further constructed different axial heterostructures doped with Si and/or Mg including n‐InGaN/n‐GaN NWs, undoped (u)‐InGaN/p‐GaN NWs, and p‐InGaN/p‐GaN NWs. [ 110 ] The optimized band structure of the p‐InGaN/p‐GaN NWs elevates anodic HER. As shown in Figure a, photo‐extracted holes accumulated on n‐InGaN/n‐GaN NWs surface readily participate in cathodic OER.…”
Section: Recent Advances Of Surface/interface Structure Modulation Onmentioning
confidence: 99%
See 1 more Smart Citation
“…Afterwards, this group further constructed different axial heterostructures doped with Si and/or Mg including n‐InGaN/n‐GaN NWs, undoped (u)‐InGaN/p‐GaN NWs, and p‐InGaN/p‐GaN NWs. [ 110 ] The optimized band structure of the p‐InGaN/p‐GaN NWs elevates anodic HER. As shown in Figure a, photo‐extracted holes accumulated on n‐InGaN/n‐GaN NWs surface readily participate in cathodic OER.…”
Section: Recent Advances Of Surface/interface Structure Modulation Onmentioning
confidence: 99%
“…d) LSV curves,and e) chronoamperometry measurements and f) hydrogen and oxygen evolution for the InGaN/GaN NWs photoelectrode (the photoanodes and photocathodes were tested in pH 7 and pH 0 electrolytes, respectively, under 6 suns AM 1.5 G illumination). Reproduced with permission [110]. Copyright 2019, The Optical Society.…”
mentioning
confidence: 99%
“…According to the previous works, however, the current density of the photoanodes using metal oxides was measured to be less than 1 mA/cm 2 and therefore, needs to be improved. Recently, a III-nitride material system has been reported as a potential candidate for PEC-WS which has the merit of possessing a tunable band gap that spans nearly the entire solar spectrum, and good corrosion resistance in aqueous solution. Among them, a GaN nanowire (NW) has been suggested as an effective medium to improve PEC-WS performance due to its large surface-to-volume ratio, strong separation of photogenerated carriers, and enhanced optical absorption coefficient. Most importantly, the conduction-band minimum (CBM) and the valence-band maximum (VBM) of GaN NWs can straddle the water redox potentials, facilitating a highly stable and efficient PEC-WS . However, III-nitride NWs have pronounced surface states, thereby providing surface Fermi-level pinning to the carriers, which leads to Shockley-Read-Hall nonradiative recombination and indirect recombination related to the radial Stark effect. , To improve the efficiency of PEC-WS, noble metals such as Pt and Au were used to reduce the effect of surface states of the GaN NWs.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Because hydrogen is generated directly at the photocathode (PC) in the PEC-WS cell, the materials used to fabricate the PC have been actively researched in an attempt to maximize the PEC-WS efficiency. 4,5 Previous representative results on PCs fabricated with various materials and structures are summarized in Table 1, [6][7][8][9][10][11][12][13][14][15][16][17][18] where the current density, applied-bias photon-to-current efficiency (ABPE), and the amount of hydrogen gas generated from the PC for the PEC-WS are less than 25 mA cm À2 , 5%, and 1.5 mmol, respectively. 10,13 Moreover, previous studies found that the performance of the PCs signicantly degraded with respect to the reaction time.…”
mentioning
confidence: 99%
“…Considering the previous representative results listed in Table 1, the current density of the InGaN/GaN-CSNW PC fabricated in the present work is much higher than those of the PCs in previous studies, irrespective of their material composition and structure. [6][7][8][9][10][11][12][13][14][15][16][17][18] Fig. 2d shows the ABPE derived from the J-V characteristic curves of the InGaN/GaN-CSNW PC.…”
mentioning
confidence: 99%